171 THE EFFECT OF SURGICAL INTERVENTION ON BIOMECHANICAL ALIGNMENT IN THE TRANSVERSE PLANE DURING WALKING IN CHILDREN WITH CEREBRAL PALSY. Issue 1 (1st January 2007) - Gurbani, B.; Fowler, E.; Oppenheim, W.
Abstract : Objective: The study evaluated the effectiveness of orthopedic surgical intervention in correcting transverse plane gait abnormalities for patients with the spastic form of cerebral palsy (CP). Background: Quantitative gait analysis is useful in identifying causes of walking abnormalities in patients with CP. One significant problem in spastic CP patients is "in-toeing, " resulting in inadequate foot clearance and tripping. Causes of "in-toeing" include femoral anteversion, internal rotation of the tibia relative to the femur, and subtalar joint inversion. With the advent of clinical gait analysis laboratories, objective kinematic and kinetic data are now used in designing an optimal course of treatment for patients. Subjects: Data were collected at the UCLA Center for Cerebral Palsy. Subjects were five patients with the spastic form of CP who had undergone orthopedic surgery to correct abnormalities of gait in the transverse plane (age range = 8-21, mean = 12.4, median = 10.8 years). All subjects and guardians provided informed consent. Methods: A retrospective records search was used to identify all pediatric patients with cerebral palsy who were recommended for orthopedic surgery to correct in-toeing. Patients who proceeded with the surgery were then identified. Gait analysis was performed at the Kameron Gait and Motion Analysis Laboratory. Eight cameras were used to capture movement after 15 reflective markers were placed on specific bony landmarks on the patients' pelvis and lower extremities. Kinematic data were calculated using OrthoTrak 6.29 (Motion Analysis Corporation, Santa Rosa, CA). Of the five subjects, two subjects underwent operations on the femur, two on the tibia, and one on the foot; three of the subjects had bilateral surgery. Postoperational gait analysis was performed an average of 16 months after surgery. The study was IRB approved. Results/Conclusions: Normalization of foot angle progression in the transverse plane during gait was the primary outcome measured. Between the five patients, a total of 8 feet was assessed. The average improvement in foot progression angle was 22.51° of external rotation, placing the foot into a more normal progression angle. Secondary improvements in knee rotation and hip rotation were also observed. Gait analysis is an established method to assess the success of orthopedic surgical interventions in patients with cerebral palsy. Following orthopedic interventions, kinematic data demonstrated an improved foot progression angle with less in-toeing and a more stable, normalized gait pattern.